2005
DOI: 10.1002/cvde.200506396
|View full text |Cite
|
Sign up to set email alerts
|

High Growth Rate of Erbium Oxide Thin Films in Atomic Layer Deposition from (CpMe)3Er and Water Precursors

Abstract: Organometallic tris(methylcyclopentadienyl)erbium and water were successfully exploited as precursors for the atomic layer deposition (ALD) of Er 2 O 3 thin films. Deposition studies were carried out in the temperature range 175±450 C, where Si(100) and soda-lime glass were used as substrates. ALD-type growth mechanism could be verified at relatively low deposition temperatures of 250 C and 300 C, where a high growth rate (1.5 per cycle) for an ALD process was obtained. The deposited Er 2 O 3 films were smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 41 publications
2
58
1
Order By: Relevance
“…The list of ALD rare-earth oxide processes (Table 3) [34,81,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] already covers all the rare-earth elements [104]. The oxygen precursor most common in ALD processes, H 2 O, does not show chemical activity sufficient for the reaction with ␤-diketonates and films could thus not be obtained using water as the precursor.…”
Section: Growth Of Binary Rare-earth Oxide Thin Filmsmentioning
confidence: 96%
“…The list of ALD rare-earth oxide processes (Table 3) [34,81,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] already covers all the rare-earth elements [104]. The oxygen precursor most common in ALD processes, H 2 O, does not show chemical activity sufficient for the reaction with ␤-diketonates and films could thus not be obtained using water as the precursor.…”
Section: Growth Of Binary Rare-earth Oxide Thin Filmsmentioning
confidence: 96%
“…Using the same Er-precursor, Päiväsaari et al reported a higher GPC while using significantly shorter dosing times. 25 These shorter dosing times can probably be related to the use of an open crucible rather than a bubbler system as used in this work. The precursor in the bubbler has a comparatively smaller surface area, and, therefore, the influence of the low precursor vapor pressure is more pronounced.…”
Section: -2mentioning
confidence: 96%
“…Päiväsaari et al reported an ALD process for Er 2 O 3 , using Er(thd) 3 and Er(CpMe) 3 as precursors, in combination with O 3 and H 2 O as oxidants, respectively. 24,25 Al 2 O 3 :Er waveguides have also been synthesized by ALD, 26 but no details on the ALD process were given. In addition, ALD has been used for Er incorporation in Y 2 O 3 by alternating the growth of Y 2 O 3 and Er 2 O 3 layers.…”
Section: Introductionmentioning
confidence: 99%
“…Among the lanthanide oxides and precursors studied in this work, Nd 9 and Er 10 have previously 30 been investigated in the temperature range 200 -450 °C, Yb 11 at 250 -400 °C, while for Sm, Eu, Dy, Ho, Tm 8 , and Tb 12 only data at 300 °C are available. The use of alternative precursors has been investigated [13][14][15][16][17][18][19][20] . Ternary oxides and nanolaminates containing lanthanides have been deposited both by using the β- 35 diketonate chelates Ln(thd) 3 (Hthd = 2,2,6,6-tetramethyl-3,5-heptanedione) 9,12,[21][22][23][24][25][26] and alternative [27][28][29] precursors.…”
mentioning
confidence: 99%